The implementation of sustainable agricultural strategies to alleviate poverty in Topiya village of Emalahleni district municipality in Mpumalanga province - Ndlovu, Robert (My University, 2015)
The study seeks to establish how sustainable agriculture can improve livelihoods and consequently alleviate poverty in Topiya community of Mpumalanga Province. The study also entails an investigation into whether the Topiya community is food insecure, and in this instance, how sustainable agriculture can be embraced smoothly to improve the food security status of the Topiya community. The study also seeks to unearth whether raising rural agricultural productivity is sufficient to improve livelihoods or a more robust and multi dimensional approach is needed to improve rural livelihoods in general. A research instrument (questionnaire) was designed and administered to 19 households. The data is analyzed by way of frequencies and percentages. The results yielded by this study demonstrated that Topiya Community is food insecure and a plethora of factors such as but not limited to lack of adequate arable land, lack of farm assets, lack understanding of the concept of sustainable agriculture contributes to this. The results also pointed to the fact that an intrinsic understanding of what sustainable agriculture entails is of paramount importance for the concept to be embraced and achieve the objectives of improving food security and consequently alleviating poverty.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. October 2014.
Keywords: Agriculture - Economic aspects.; Food industry and trade.; Food security.; Sustainable agriculture.; Food supply - South Africa - Mpumalanga.